Attention-deficit hyperactivity disorder in Egyptian medical students and how it relates to their academic performance - Eman M Shebl; Noha M. Abu Bakr Elsaid; Hend A Hassan; Doaa Kamal; Eman Araby (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: The neurobehavioral disorder, known as attention-deficit hyperactivity disorder (ADHD), is characterized by impulsivity, hyperactivity, and a lack of focus. In addition, it is connected to poor academic performance. The purpose of this study was to determine the prevalence of ADHD and its effect on their academic performance among medical students. MATERIALS AND METHODS: This web-based cross-sectional study was conducted among medical students of four medical colleges during December 2021 and April 2022. Data was collected using a self-administered questionnaire comprising Wender Utah Rating Scale and adult ADHD Self-Report Scale [ASRS]. The link to Google Form survey was distributed to students through academic emails and WhatsApp. Data analyzed using SPSS; Chisquare test or Fisher's exact test as appropriate, were used to determine statistical significance. RESULTS: A total of 990 students filled online questionnaire; 54.7% were females.. The estimated prevalence of ADHD in Egyptian medical students was 11%. Students who had childhood ADHD were significantly linked with the present ADHD (r = 0.54, P < 0.001). There was a negative correlation between the ASRS score for ADHD and students' GPA (r = 0.2, P < 0.001). No statistically significant association was observed between ADHD and sex, type of university, and academic level. of the students. CONCLUSION: ADHD is prevalent among medical students. Since most of our students with adult ADHD also had preexisting childhood ADHD, it is crucial that the primary care services, especially school health services, have appropriate standards for the early identification and management of ADHD. Health authorities should conduct a comprehensive health education campaign to raise public awareness of ADHD and its risk factors, the clinical picture, and the burden.